Metabolomic and transcriptomic signatures of influenza vaccine response in healthy young and older adults - Chou, Chih‐Hung; Mohanty, Subhasis; Kang, Heather A.; Kong, Lingjia; Avila‐Pacheco, Julian; Joshi, Samit R.; Ueda, Ikuyo; Devine, Lesley; Raddassi, Khadir; Pierce, Kerry; Jeanfavre, Sarah; Bullock, Kevin; et al. (Aging cell, 2022)
Seasonal influenza causes mild to severe respiratory infections and significant morbidity, especially in older adults. Transcriptomic analysis in populations across multiple flu seasons has provided insights into the molecular determinants of vaccine response. Still, the metabolic changes that underlie the immune response to influenza vaccination remain poorly characterized. We performed untargeted metabolomics to analyze plasma metabolites in a cohort of younger and older subjects before and after influenza vaccination to identify vaccine‐induced molecular signatures. Metabolomic and transcriptomic data were combined to define networks of gene and metabolic signatures indicative of high and low antibody response in these individuals. We observed age‐related differences in metabolic baselines and signatures of antibody response to influenza vaccination and the abundance of α‐linolenic and linoleic acids, sterol esters, fatty‐acylcarnitines, and triacylglycerol metabolism. We identified a metabolomic signature associated with age‐dependent vaccine response, finding increased tryptophan and decreased polyunsaturated fatty acids (PUFAs) in young high responders (HRs), while fatty acid synthesis and cholesteryl esters accumulated in older HRs. Integrated metabolomic and transcriptomic analysis shows that depletion of PUFAs, which are building blocks for prostaglandins and other lipid immunomodulators, in young HR subjects at Day 28 is related to a robust immune response to influenza vaccination. Increased glycerophospholipid levels were associated with an inflammatory response in older HRs to flu vaccination. This multi‐omics approach uncovered age‐related molecular markers associated with influenza vaccine response and provides insight into vaccine‐induced metabolic responses that may help guide development of more effective influenza vaccines. Seasonal influenza causes respiratory infections and significant morbidity, especially in older adults, and response to flu vaccine remains particularly poor among this population. We performed untargeted plasma metabolomics and transcriptomics in a cohort of younger and older subjects before and after influenza vaccination. We identified age‐ and vaccine‐related molecular markers associated with vaccine response, insights which may guide development of improved influenza vaccines.